Colovesical fistula: A rare cause of recurrent urinary tract infection in young male managed conservatively - Kadam, Swapnil; Kundargi, Vinay S; Patil, Siddangouda; Patil, Basavesh; Guru, Nilesh; Jain, Anuj (Indian Journal of Case Reports, 2019)
Colovesical fistula is a rare disease which has abnormal communication between the colon and urinary bladder, and it is most commonly caused by diverticular disease. A 25-year-old male was presented with recurrent episodes of dysuria since last 3 yearrs. Further examination revealed that he had associated bowel complaints of frequent stools and intermittent loose stools, which further subsided on taking antibiotics. Colonoscopy was performed which revealed inflamed colonic mucosa. The Biopsy was taken from the concerned region which suggested chronic nonspecific inflammation. Medical management can be considered in patients with colovesical fistula who are willing for long term surveillance.